Корреляция параметров арсенид-галлиевых эпитаксиальных слоев и технологии их выращивания - Karimov, A. V.; Yodgorova, D. M.; Yakubov, E. N. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The correlation between mobility and carriers concentration and growth’s conditions of gallium arsenic layers by liquid phase epitaxy is established. It is possible to obtain layers with required mobility and concentration of charge carriers by changing of technology parameters of growth’s process.